2022
DOI: 10.1097/gox.0000000000004180
|View full text |Cite
|
Sign up to set email alerts
|

Implant-based versus Autologous Reconstruction after Mastectomy for Breast Cancer: A Systematic Review and Meta-analysis

Abstract: Background: For women undergoing breast reconstruction after mastectomy, the comparative benefits and harms of implant-based reconstruction (IBR) and autologous reconstruction (AR) are not well known. We performed a systematic review with meta-analysis of IBR versus AR after mastectomy for breast cancer. Methods: We searched Medline, Embase, Cochrane CENTRAL, CINAHL, and ClinicalTrials.gov for studies from inception to March 23, 2021. We assessed the risk of bias of individual studies and strength of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 68 publications
3
39
0
Order By: Relevance
“…The previously reported rates of postmastectomy reconstruction in the United States have been 19% autologous and 81% implant-based reconstruction, with 68% undergoing two-stage allogenic reconstruction, and 13% undergoing one-stage (direct-to-implant) reconstruction, which is comparable to our data. 24 Overall rates of complications were also similar to previous studies of breast reconstruction after mastectomy. 17,18,25 National and statewide studies had previously demonstrated that greater travel distance had a negative impact on the rate of breast reconstruction after mastectomy, with patients who underwent reconstruction traveling father than those who did not, especially to academic institutions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The previously reported rates of postmastectomy reconstruction in the United States have been 19% autologous and 81% implant-based reconstruction, with 68% undergoing two-stage allogenic reconstruction, and 13% undergoing one-stage (direct-to-implant) reconstruction, which is comparable to our data. 24 Overall rates of complications were also similar to previous studies of breast reconstruction after mastectomy. 17,18,25 National and statewide studies had previously demonstrated that greater travel distance had a negative impact on the rate of breast reconstruction after mastectomy, with patients who underwent reconstruction traveling father than those who did not, especially to academic institutions.…”
Section: Discussionsupporting
confidence: 86%
“…Approximately half (52.6%) of all mastectomy patients underwent breast reconstruction, which is comparable to previous literature demonstrating a postmastectomy reconstruction rate of 40%. 4,[21][22][23][24] Most of the patients who underwent reconstruction had immediate two-stage allogenic reconstruction, with 23.9% of patients undergoing autologous reconstruction. The previously reported rates of postmastectomy reconstruction in the United States have been 19% autologous and 81% implant-based reconstruction, with 68% undergoing two-stage allogenic reconstruction, and 13% undergoing one-stage (direct-to-implant) reconstruction, which is comparable to our data.…”
Section: Discussionmentioning
confidence: 99%
“…Companion articles focus on implant-based reconstruction 4 and the comparison between implant-based reconstruction and AR. 5 All reports focus on women undergoing (or who have undergone) mastectomy for breast cancer treatment or prophylaxis. Here, we evaluate the comparative benefits and harms of (1) timing of AR relative to chemotherapy and radiation therapy, and (2) various flap types for AR.…”
mentioning
confidence: 99%
“…Thanks to the development of the Breast-Q, patient-reported outcomes in breast reconstruction have widely been explored, while the health-related quality of life (HRQoL) and symptoms of depression have been neglected (8,9). Studies giving a comprehensive overview of further clinical and surgical outcome parameters such as complication rates, aesthetic outcome, and breast sensibility of both procedures are lacking (8,(10)(11)(12). Furthermore, most studies do not include a homogenous patient collective with regard to the type of mastectomy (6,10), which makes the interpretation of the study results difficult (8).…”
Section: Introductionmentioning
confidence: 99%